PELATIHAN PEMBUATAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN BERBASIS WEBSITE BAGI GURU SMK CENDEKIA MADIUN - Susanti, Pratiwi; Jayadi, Puguh; Hidayati, Nasrul Rofiah; Riyanto, Slamet; Kiswardianta, R. Bekti (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Learning in the current era has implemented ICT-based learning. Therefore, teachers are required to master technology in the teaching and learning process. The importance of increasing the competence and skills of teachers in utilizing and maximizing ICT-based learning media so that it is necessary to hold training in creating and using ICT-based learning media for teachers. The training carried out carrying the title